2019
DOI: 10.1111/1749-4877.12352
|View full text |Cite
|
Sign up to set email alerts
|

Synteny search identifies carnivore Y chromosome for evolution of male specific genes

Abstract: The explosively accumulated mammalian genomes have provided a valuable resource to characterize the evolution of the Y chromosome. Unexpectedly, the Y-chromosome sequence has been characterized in only a small handful of species, with a majority of them being model organisms. Thus, identification of Y-linked scaffolds from unordered genome sequences is becoming more important. Here, we used a syntenic-based approach to generate the scaffolds of male specific region in Y chromosome (MSY) from the genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The importance of these Y-linked genes during male development has been elucidated for mammals [31][32][33][34]. These genes are located in the non-recombining region of the Y chromosome (NRY), which is also known as the male-specific Y (MSY) region, transmitted from fathers to sons without recombination with the X chromosome [35]. The MSY region contains only 27 genes coding for distinct proteins, as the SRY, EIF1AY, KDM5D, ZFY, EIF2S3Y, and DDX3Y [31,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these Y-linked genes during male development has been elucidated for mammals [31][32][33][34]. These genes are located in the non-recombining region of the Y chromosome (NRY), which is also known as the male-specific Y (MSY) region, transmitted from fathers to sons without recombination with the X chromosome [35]. The MSY region contains only 27 genes coding for distinct proteins, as the SRY, EIF1AY, KDM5D, ZFY, EIF2S3Y, and DDX3Y [31,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we de novo sequenced a wild male red panda genome (15), which enabled us to develop Y chromosome SNPs. Using a genome synteny searching strategy and the female dog genome (boxer breed) and the dog male-specific Y chromosome sequences (Doberman breed) as the reference, Fan et al recently identified a set of nine male-specific Y chromosome scaffolds with a total length of 964 kb from the male red panda genome assembly (table S5) (31). Using the 964-kb male-specific Y chromosome scaffolds as the reference, we aligned the whole-genome resequencing reads of 18 male red pandas to the reference genome using BWA and then performed SNP calling using SAMtools and GATK.…”
Section: Identification and Genotyping Of Y Chromosome Snpsmentioning
confidence: 99%
“…In total, 22 scaffolds of 5 Kbp or longer were found to contain an MSY gene or gene fragment. Putative Y-chromosome orthologs were identified for all 11 core carnivore MSY genes [31].…”
Section: Resultsmentioning
confidence: 99%
“…Research in well-developed mammalian genomic models such as dog and cat [6,7,35] facilitated the identification of red fox orthologs of carnivore MSY genes. Out of 18 dog MSY genes analyzed, 17 were identified in putative Y-linked red fox scaffolds, including all 11 of the core carnivore MSY genes [31]. The only dog protein that was not assigned a position in the fox scaffolds was TSPY .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation